Decision-making on determining the direction of strategic development of the enterprise within the limits of diversifying its activities - Zalutska, Khrystyna; Maslak, Tetyana; Kosobutskyi, Mykola; Stefantsov, Dmytro (Technology audit and production reserves, 2025)
The object of research is the process of determining the direction of strategic development of an enterprise depending on its strategic capability and orientation. It is determined that the basis for the operational choice of the strategic direction of the enterprise's development is the supporting information, which is formed on the basis of key aspects of the existence of the enterprise and determines its strategic orientation. It is substantiated that the strategic orientation outlines the fundamental principles of the enterprise's functioning, which is the basis for determining the competitive advantages necessary for its sustainable development in the strategic period. It is revealed that the specification of the strategic orientation by the current results of the influence of environmental factors on the enterprise's functioning allows to outline its strategic capability. It is proved that the level of strategic capability determines the ability of the enterprise to form and implement a certain direction of strategic development. The features of the calculation and the scale for determining the level of the enterprise's strategic capability are presented. An improved approach to forming/adjusting the direction of the enterprise's strategic development, taking into account its strategic capability and strategic capability, is proposed. The results of the practical application of the recommendations in the activities of the representative enterprise confirmed their effectiveness in terms of efficiency and clarity of the outline of the strategic direction of development. The main and intermediate values of the integral indicator of strategic capability allowed to choose a hybrid direction of development of the enterprise. The chosen direction of strategic development provided the studied enterprise with growth and income from the cultivation of new types of crops – rapeseed with a production profitability of 24.8 %, a yield of 31 centners/hectare, an additional net income of 18,75 thousand dollars and organic crops.